How do you solve 3( x - 1) - 2x - 3+ 15= \frac { 4x - 1} { 3} + x + \frac { 1} { 12}?

2 Answers
Nov 22, 2017

x=111/16

Explanation:

3(x-1)-2x-3+15={4x-1}/3+x+1/12

3x-3-2x-3+15={4x-1}/3+x+1/12

x+9={4x-1}/3+x+1/12

9={4x-1}/3+1/12

108=16x-4+1

16x=111

x=111/16

Nov 22, 2017

The answer is x = 111/16

Explanation:

We have the question

3(x-1) - 2x -3 + 15 = "4x-1"/3 + x + 1/12

Removing the parentheses,

We get,

3x-3 - 2x -3 + 15 = "4x-1"/3 + x + 1/12

From addition and subtraction of 'similar' terms. We get,

x+9 = "7x-1"/3 +1/12

Now separating keeping similar terms in one side. We have,

9 - 1/12 = "7x-1"/3 - x

(Note: The change in sign occurs due to the shifting of term from one side to the other)

Now by simplifying,

107/12 = "4x-1"/3

Multiplying both sides by 12. We get,

107/12 * 12 = "4x-1"/3 * 12

or 107 = 16x -4

Adding 4 to both sides. We get,

or 107 +4 = 16x -4 +4

or 111 = 16x

Now dividing both sides by 16. We get,

or 111/16 = "16x"/16

Thus, Giving

x = 111/16